Qualitative Study Protocol: Augmented Reality Technology to Deliver Asthma Inhaler Technique Training for Children and Adolescents With Asthma. (10th September 2021) - O'Connor, Antonia; Tai, Andrew; Kopsaftis, Zoe; Carson-Chahhoud, Kristin
Asthma is a chronic inflammatory condition of the airways with a heterogenous symptom profile. When symptoms are poorly controlled and frequent, asthma sufferers are impacted regularly, with limitations on physical activities and sleep disturbances, significantly impairing quality of life. Asthma is highly prevalent and the leading cause of disease burden in young people. Those aged 0–14 contribute to over half of the asthma hospitalisations within Australia. Asthma education and self-management remains a key component of care; however, challenges remain in the paediatric population with difficulties of engagement. Augmented reality (AR) may provide a novel and effective solution with its ability to superimpose virtual objects into a real-world setting. Using a smartphone or tablet to deliver AR makes this modality accessible to much of the population. AR is a growing field in technology and has already established uses in education and training. The ability to increase motivation, enhance enjoyment and encourage faster concept understanding in the educational setting is encouraging and supports our proposal that AR technology can provide a generation appropriate education delivery modality for young people with asthma. To ensure successful implementation of an AR asthma educational resource on a large scale, the usability, acceptability, barriers and enablers of its use must be investigated. Using an iterative co-design process, an asthma resource utilising AR to deliver education on inhaler technique will be created. Qualitative research will be undertaken using semi-structured interviews with moderator guides to obtain mixed-method data on the AR resource. Participants will be key members of the asthma community including children and adolescents with asthma (8–17 years old), caregivers of children and adolescents with asthma, and health professionals. Understanding the usability, acceptability, barriers and enablers of the AR resource will enable us to improve our alpha version and test an optimal version in a planned feasibility study.